PalmHashing: a novel approach for cancelable biometrics - Tee, Connie; Teoh, Andrew Beng Jin; Goh, Michael Kah Ong; Ngo, David Chek Ling (Elsevier Science, 2005)
We propose a novel cancelable biometric approach, known as PalmHashing, to solve the non-revocable biometric issue. The proposed method hashes palmprint templates with a set of pseudo-random keys to obtain a unique code called palmhash. The palmhash code can be stored in portable devices such tokens and smartcards for verification. Multiple sets of palmbash codes can be maintained in multiple applications. Thus the privacy and security of the applications can be greatly enhanced. When compromised, revocation can also be achieved via direct replacement of a new set of palmhash code. In addition, PalmHashing offers several advantages over contemporary biometric approaches such as clear separation of the genuine-imposter populations and zero EER occurrences. In this paper, we outline the implementation details of this method and also highlight its potentials in security-critical applications. (C) 2004 Elsevier B.V. All rights reserved.